Doodleville. Art attacks! - Sell, Chad (New York : Alfred A. Knopf, 2022)
Drew never meant for this to happen. She didn't mean for her doodle Mike to steal the centuries-old hat. She didn't mean for Levi to steal the centuries-old baby (when he was supposed to be returning the coveted hat!). And she definitely didn't mean to send the Art Institute of Chicago into a downward spiral of art-on-art combat. She just wanted to fix a simple mistake! Now everything's gone wrong, and it's mayhem at the museum.
2.8
3-6
GN240L
Keywords: Doodles -- Comic books, strips, etc; Monsters -- Comic books, strips, etc; Monsters -- Juvenile fiction; Artists -- Comic books, strips, etc; Artists -- Juvenile fiction; Monsters -- Fiction; Artists -- Fiction; Monster comics; Graphic novels; Comics (Graphic works)